A room with a view (England : Merchant Ivory Productions for Goldcrest, 1985)
Nominated for eight Oscars in 1986, including Best Picture, and winner of three (Costumes, Art Direction and Adapted Screenplay), A Room With a View is the film that defined Merchant-Ivory as the masters of the romantic period piece. A brilliant adaptation of E.M. Forster's novel, A Room With a View tells the story of the coming of age of Lucy Honeychurch (Helena Bonham-Carter). Longing to burst free from the repression of British upper class manners and mores, she must wrestle with her inner romantic longings to choose between the passionate George (Julian Sands) and the priggish but socially suitable Cecil (Daniel Day-Lewis). Boasting a brilliant supporting cast, A Room With a View isone of the most romantic of romantic comedies ever filmed.
directed by James Ivory; produced by Ismail Merchant edited by Humphrey Dixon
Maggie Smith, Denholm Elliot, Judi Dench, Simon Callow, Helena Bonham Carter, Julian Sands, Daniel Day Lewis